2001
DOI: 10.1107/s090744490101040x
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of theBacillus thuringiensistoxin Cry1Ac and its complex with the receptor ligandN-acetyl-D-galactosamine

Abstract: Cry1Ac from Bacillus thuringiensis ssp. kurstaki HD-73 is a pore-forming protein specifically toxic to lepidopteran insect larvae. It binds to the cell-surface receptor aminopeptidase N in Manduca sexta midgut via the sugar N-acetyl-D-galactosamine (GalNAc). By using 1,3-diaminopropane (DAP) as the buffer throughout protoxin activation and chromatography on Q-Sepharose at pH 10.3, trypsin-activated Cry1Ac has been purified in a monomeric state, which was crucial to obtaining single crystals of Cry1Ac and of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 24 publications
0
49
0
Order By: Relevance
“…Domain III shows less structural variability than domain II, and the main differences are found in the lengths, orientations, and sequences of the loops (11). The importance of these differences is particularly evident with Cry1Aa and Cry1Ac, where a loop extension in Cry1Ac creates a unique N-acetylgalactosamine (GalNAc) binding pocket implicated in receptor binding (21,32,108). Domain III has been compared to a number of different proteins (28), but its similarity to carbohydrate-binding modules (CBMs) found in microbial glycoside hydrolases, lyases, and esterases is particularly striking.…”
Section: Toxin Structure and Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…Domain III shows less structural variability than domain II, and the main differences are found in the lengths, orientations, and sequences of the loops (11). The importance of these differences is particularly evident with Cry1Aa and Cry1Ac, where a loop extension in Cry1Ac creates a unique N-acetylgalactosamine (GalNAc) binding pocket implicated in receptor binding (21,32,108). Domain III has been compared to a number of different proteins (28), but its similarity to carbohydrate-binding modules (CBMs) found in microbial glycoside hydrolases, lyases, and esterases is particularly striking.…”
Section: Toxin Structure and Functionmentioning
confidence: 99%
“…Jenkins et al showed that mutants with alanine substitutions at Q509, R511, Y513, or 509 QNR 511 failed to bind to purified M. sexta APN (81) and bound to purified L. dispar APN with lower affinity (82). The crystal structure of Cry1Ac, solved in the presence and absence of GalNAc, has helped to further characterize the domain III APN binding site and has provided a structural explanation for why Cry1Ac, but not Cry1Aa, binds to APN in a manner dependent on GalNAc (32,108). Analysis of the structure revealed a unique 6-residue insertion ( 505 GNNIQ N 510 ) in domain III that was not observed in Cry1Aa and was not predicted by an automatically generated model of Cry1Ac (81).…”
Section: Other Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the Cry1Ac toxin lacks ester bonds there are nevertheless biochemical mechanisms mediated by glycan interactions by which it could bind to esterases as proposed by Gunning et al 69,78) Cry1Ac is known to have high affinity for N-acetyl galactosamine (GalNAc) moieties on proteins 80) and indeed the mechanism of action of the toxin is believed to involve its binding to GalNAc moieties on aminopeptidases which are localised to the larval gut wall via glycosylphosphotidylinositol (GPI) anchors. 81) Sublethal doses of Cry1Ac are also known to lead to the specific shedding and excretion of GPI-anchored proteins from lepidopteran larval guts.…”
Section: Heliothine Resistance To Other Insecticidesmentioning
confidence: 99%
“…To date, the X-ray crystal structures of several Cry dendotoxins Cry3Aa [12], Cry1Aa [13], Cry1Ac [36], Cry2Aa [37] and Cry3Bb [38] have been elucidated. Although these Cry toxins exert their specific toxicity against different target insect larvae, they display a high degree of overall 3D structural similarity, consisting of three distinct domains.…”
Section: D Structure and Functional Prediction Of Cry1i And Cry3a Prmentioning
confidence: 99%